Are climate change risks priced in the U.S. Stock market? - Renato Faccini; Rastin Matin; George Skiadopoulos (Danmarks Nationalbank, 2021)
We construct novel proxies of physical and transition climate risks by conducting textual analysis of climate-change news over the period 2000-2018. This analysis uncovers four textual variables related to the topics of U.S. climate policy, international summits, natural disasters, and global warming, respectively. The first two variables proxy transition risks, whereas the last two proxy physical risks. We find that only the climate policy factor is priced in the U.S. stock market with the evidence being more pronounced over 2012-2018. The documented premium is consistent with the idea that investors hedge short-term transition risks. We validate this explanation using a narrative approach to measuring climate news. Our results imply that investors' attention is an important driver of asset returns
Keywords: C63; G12; Q5; 330; Climate; Financial Stability; Statistical Method